Karakteristik Campuran Teh Hitam (Camellia sinensis) dan Daun Kayu Manis (Cinnamomum burmannii) - Rahayu Suseno; Sur haini; Naufal Bintang Setiyandi (Jurnal Pangan dan Gizi, 2023)
This study was conducted to determine the effect of the comparison of black tea (Camellia sinensis) and cinnamon leaves (Cinnamomum burmannii) on the physicochemical and organoleptic properties of the tea brewed. This study used a completely randomized design (CRD) with a ratio of black tea(%) and cinnamon leaves(%) as treatment, with 5 treatment levels, namely 90:10; 80:20; 70;30; 60:40; and 50:50, each treatment was repeated 4 times to obtain 20 experimental units. Parameters observed included color degree, pH, antioxidant activity, total phenols, total tannins, and organoleptic properties (hedonic quality in aroma, taste, and color, as well as hedonic overall acceptance and multiple ratios). Mixing tea with a ratio of 70% black tea and 30% cinnamon leaves was the best treatment with an antioxidant activity value of 76.46, total phenol 199.31 mg GAE/g, total tannins 114.69 mg TAE/g, pH value 6, 11, color values L* (32.25), a* (26.75), and b* (37.75) with a description of dark orange color, hedonic quality of color 3.44 (slightly deep red), hedonic quality of aroma 3 .72 (a mixture of black tea and cinnamon leaves), hedonic taste 2.84 (not astringent), overall acceptance hedonic 4.16 (likes), and plural ratio 6.16 (better than R).